Multiple Use of Forests - Tuulentie, Seija; Bjärstig, Therese; Hansen, Inger; Lande, Unni; McLean, Paul; Pellikka, Jani; Peltola, Rainer; Zhang, Jasmine (Springer Nature Switzerland, 2025)
Sustainable forest management approaches, regardless of whether they involve continuous cover forestry (CCF) or rotation forestry (RF), require a holistic landscape perspective that acknowledges the multiple interests, values, and uses that depend on the locally relevant economic, ecological, and socio-cultural circumstances. These must be considered alongside the use of forests and forest landscapes as a resource for rural development. Forests provide a wide range of goods and services. Those addressed here (i.e. tourism, recreation, health, grazing, non-timber forest products, and societal protection from natural hazards) are a subset of all of those potential services that are already considered to be of special significance for the Nordic region. Most recreational users consider variation in the forest landscape and long-distance views as visually attractive but think that clearcuttings and soil tilling are harmful. In general, CCF favours bilberries, while lingonberries and some mushrooms benefit from even-aged forestry. Owing to the many and varied demands relating to forests and forest landscapes in Norway, Sweden, and Finland, CCF-supported multiple-use strategies and planning will need to consider stakeholder requirements more, now and in the future, than is currently the case.
Keywords: recreation; nature-based tourism; grazing; non-timber forest products; natural hazards